2019
DOI: 10.1016/j.jns.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

A score using left ventricular diastolic dysfunction to predict 90-day mortality in acute ischemic stroke: The DONE score

Abstract: The aim of this study was to identify whether diastolic dysfunction predicts death at 90 days after acute ischemic stroke. Methods: We retrospectively analyzed patients with ischemic stroke. All patients underwent transthoracic echocardiography to evaluate systolic function and diastolic function by means of assessing ejection fraction and septal E/e'. We evaluated the initial National Institute of Health Stroke Scale (NIHSS) score, arterial occlusion, and laboratory data. We used multivariate regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The total of all these scores (Total Point axis) can then be used to determine the predicted 10-year mortality (10-year Mortality axis) been externally validated. Data unavailability and limited resources can be a potential obstacle in wider adoption of these scores, which can be the case with some of the models including biomarkers [44] or those using imaging data [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total of all these scores (Total Point axis) can then be used to determine the predicted 10-year mortality (10-year Mortality axis) been externally validated. Data unavailability and limited resources can be a potential obstacle in wider adoption of these scores, which can be the case with some of the models including biomarkers [44] or those using imaging data [45].…”
Section: Discussionmentioning
confidence: 99%
“…A review of acute stroke prediction models [ 6 ] such as iSCORE, SOAR, PLAN and THRIVE amongst others, concluded that practical aspects of the score can be potentially a limiting factor in the clinical usage of the scores, as the majority of them have a good predictive accuracy and have been externally validated. Data unavailability and limited resources can be a potential obstacle in wider adoption of these scores, which can be the case with some of the models including biomarkers [ 44 ] or those using imaging data [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thalamic strokes, located in the posterior cerebral artery (PCA) region, can cause disturbance of the autonomic nervous system in Takotsubo cardiomyopathy ( 7 ). The nucleus ambiguous and nucleus dorsalis, located in the basilar artery (BA) region, convey parasympathetic modulation of the central cardiovascular system ( 8 ). In the event of a stroke, the balance between parasympathetic and sympathetic modulation is disrupted, leading to the coronary artery spasm and myocardial ischemia ( 9 ).…”
Section: Introductionmentioning
confidence: 99%